Re-visiting the ATA 2015 sonographic guidelines - who are we missing?: A retrospective review - D. S. Chan; K. Gong; M. G. Roskies; V. I. Forest; M. P. Hier; R. J. Payne (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The American Thyroid Association published revised guidelines in 2015 on the management of differentiated thyroid cancer in adults. One of the key changes introduced in the revision proposes that diagnostic biopsy be based on ultrasound findings (i.e. size and nodule characteristics). The overall effect of these changes results in fewer nodules requiring biopsy. This study was conducted to determine if the changes to the guidelines will result in overlooked thyroid cancers, specifically malignancies with aggressive characteristics measuring between 1 and 1.49 cm. Methods Patients (n = 2083) with thyroid nodules who underwent total or subtotal/hemi thyroidectomy with or without neck dissection by a single surgeon between 2006 and 2016 were retrospectively enrolled. Demographic information and nodule characteristics were collected for all patients. Ultrasonography and final pathology reports were reviewed for patients with thyroid nodules between the sizes of 1–1.49 cm (n = 155). Results 45% (n = 70) of patients with nodules between 1 and 1.49 cm were “low suspicion” nodules according to ultrasound. 47 of these nodules contained malignancies on final histopathological examination, 100% of which were of the papillary subtype. 21% (n = 10) of these malignant nodules demonstrated extrathyroidal extension and 34% (n = 16) were associated with regional metastases. Conclusions Reliance on sonographic patterns alone could result in missed cancer diagnoses in patients with thyroid nodules measuring between 1 and 1.49 cm. Moreover, a portion of these malignancies may be associated with aggressive features. The effect of this finding on long-term outcomes is unclear.